Legal remedies in the new Law on General Administrative Procedure - Lončar, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Although the new Law on General Administrative Procedure of 2016, which has become fully applicable in June 1, 2017, abounds with novelties considering the legal remedies, it can be said that the actual level of legal protection of the parties in the administrative procedure is significantly improved, comparing to the solutions from the previous Law. Despite the fact that objection has been introduced, as a new regular legal remedy with devolution character, which can be used in all new administrative activities subordinated to administrative matters (administrative contracts, administrative actions, provision of public services), in cases when there is no other legal remedy in the administrative procedure, and considering that the system of extraordinary legal protection of the parties has been completely changed, the appeal continues to be the basic and most important mean of legal protection of the parties from unlawful and incomplete administrative acts, as the most important manifestations of administrative activity. Therefore, in order to improve the level of legal protection of parties in the administrative procedure, it has exceptional importance that the legal regime of appeal in the new Law has been significantly enhanced by the introduction of many new procedural solutions.